‘Smashing crockery’ : objets cassés, objets-déchets dans la poésie de Derek Mahon - Marion Naugrette-Fournier (Interfaces)
Throughout his poetic œuvre the Northern Irish poet Derek Mahon has made the tabula rasa a true ars poetica of his very own, using discarded objects or even ‘breaking’ objects in good condition, in order to salvage them or recycle them by reintegrating them to a new system of objects of which he alone knows the rules. To achieve such a goal, in his poems Mahon has relentlessly re-envisioned the value of an object economically, metaphysically and poetically, by temporarily destroying it. This ‘tabula rasa’ phase is thus seen as almost essential to the process of re-evaluating the value of objects, which in turn is followed by a process of reconstructing them, implying the poet’s gathering of what Donald W. Winnicott names ‘transitional objects’. Mahon’s transitional objects, so to speak, act as new toys he has made his own, so that he could be free from any kind of attachment towards a community, and especially a Northern Irish one. Mahon’s poetry is thus a ‘Building Site’ of sorts, always in motion.